Intraday returns patterns of Malaysian common stock - Mohammed Zain Yusof; Fauzias Mat Nor; Othman Yong (Penerbit Universiti Kebangsaan Malaysia, 1995)
This study examines the intraday return and risk behavior of Malaysian stock· prices. The volatility of the return is greater in the morning session for both period A and period B as measured by the standard deviation ratios. It is also obsenJed that the intraday standard deviations showed two distinct U-shaped curves for Period A (where trading started at 10. OOam and ended at 4.00pm) and also a U-shaped curve intraday for period B (where trading started at 9.30pm and ended at 5.00pm). The rank correlation which affects index return volatility is also observed. These observed volatility especially in the later period (period B) seems to be consistent with the rational trading noise hypothesis as proposed by Kyle (1985), where insider s private information is assimilated into prices by the end of the trading session.